The Influence of Social Norms on The Behaviour of Farmer Business Credit - Santoso, Aprih; Kuswardani, Diah Cori; Yani, Tri Endang; Nurhayati; Kusnilawati, Nunik (School of Business, Bogor Agricultural University (SB-IPB), 2023)
This study is important because an individual does certain behaviors if important people in his life can accept his behavior and he can accept what he will do, including taking Farmer Business Credit (KUT), so that he does not make mistakes by controlling his behavior later. This study aimed to investigate the effect of social norms on farmers' Farmer Business Credit (KUT) behavior in Kendal Regency, Patean Subdistrict, Central Java as a mediating variable. The research population included all farmers who took KUT in the Patean subdistrict, Kendal Regency, Central Java, totaling 128 people, and all of them were used as samples. Hence, the sample selection method was the census method. The AMOS-25 program analyzed data. The results show that social norms positively and significantly impact the behavior of KUT indebtedness to farmers in the Patean subdistrict, Kendal Regency, Central Java. Interest in debt can mediate the impact of social norms on the behavior of KUT indebted to farmers in the Patean subdistrict, Kendal Regency, Central Java. The managerial implication of the research is that it will provide an understanding of the importance of knowing the factors that influence farmers on the behavior of taking and managing businesses well in supporting the development of their farming business. Keywords: social norms, farming business, farmer business credit, behaviors, AMOS